Fibre Bragg grating vibration sensing system / Shirley Diong Chea Fong - Diong, Shirley Chea Fong (2014)
In the recent decades, optical fibre sensors have become more reputational due to the fact that they are small in size, robust, light weight, immune to electromagnetic field and able to multiplex. This research report presents a nonlinear output response of an acousto-optically modulated distributed Bragg reflector (DBR). DBR used in this project is fabricated from two fibre Bragg gratings (FBGs) with similar Bragg wavelength, high reflectivity and slightly different bandwidth and a 12cm erbium-doped optical fibre. This structure of DBR is able to provide good throughput power. When impinged with acoustic waves, DBR gave an astounding result over the frequency range of 130 kHz to 190 kHz and power density of the ultrasound signal. The distorted output signal observed in the experiment matches the theoretical calculations based on transfer matrix method perfectly. Also, it is discovered that the distorted output signal generates second harmonic components. At higher amplitudes, amplitude of generated second harmonic will supersede the fundamental frequency. This finding is important for understanding the acousto-optic behaviour of DBR.